Isolation and characterization of Candida metapsilosis from foci of chronic pododermatitis in captive steppe eagles in Kazakhstan - Elena Kukhar; Gulshat Bailina; Aziza Nessipbayeva; Rano Sattarova; Marat Turkeyev (PLoS ONE, 2026)
Pododermatitis (bumblefoot) is a chronic, debilitating disease of the plantar surface of the foot that affects birds of prey kept in captivity worldwide. Although bacterial pathogens, especially Staphylococcus aureus , are most commonly considered as causative agents, the contribution of opportunistic yeasts to chronic, non-healing footpad lesions remains poorly characterized. Keratinophilic yeasts may sustain the disease process by degrading keratin in superficial tissues, impairing wound healing and, owing to their thermotolerance and minimal nutritional requirements, persisting in the environment of the bird’s enclosure. In this study, three captive steppe eagles ( Aquila nipalensis ) from a single aviary in Kazakhstan, all presenting with chronic pododermatitis unresponsive to antibacterial treatment, were investigated by integrated mycological, biochemical and molecular approaches. The yeast isolates were recovered from the deep footpad lesions and identified to species level by sequencing of the ITS1-5.8S-ITS2 rDNA region. All these isolates were assigned to Candida metapsilosis , and phylogenetic analysis confirmed their close clustering with reference C. metapsilosis sequences. Phenotypic characterization showed that all isolates were thermotolerant (growth at 8–37 °C), expressed strong urease and keratinolytic activity (the latter confirmed in vitro by the hair perforation test), high saccharolytic activity and selective, weak proteolytic activity. Disk diffusion screening showed susceptibility to azoles (ketoconazole, clotrimazole, fluconazole) and reduced susceptibility to polyenes (nystatin, amphotericin B). To our knowledge, this is the first report of C. metapsilosis isolated from chronic pododermatitis lesions in captive steppe eagles. Combined with the documented in vitro virulence-associated traits and the resolution of the lesions following targeted antifungal therapy, our findings support a contributory etiological role of C. metapsilosis as an opportunistic pathogen in raptor pododermatitis in immunocompromised birds maintained under suboptimal husbandry. Mycological work-up, including molecular identification, is therefore warranted in cases of chronic, non-resolving pododermatitis in captive birds of prey.